International Survey on the Management of Congenital Diaphragmatic Hernia - Zani, Augusto; Eaton, Simon; Puri, Prem; Rintala, Risto; Lukac, Marija; Bagolan, Pietro; Kuebler, Joachim F.; Friedmacher, Florian; Hoellwarth, Michael E.; Wijnen, Rene; Tovar, Juan A.; Pierro, Agostino; on behalf of the EUPSA Network Office (European Journal of Pediatric Surgery, 2016)
Aim This study aims to define patterns in the management of congenital diaphragmatic hernia (CDH).Methods A total of 180 delegates (77% senior surgeons) from 44 (26 European) countries completed a survey at the 2014 European Pediatric Surgeons' Association meeting.Results Overall, 34% of the surgeons work in centers that treat < 5 cases of CDH/y, 38% work in centers that treat 5 to 10 cases/y, and 28% work in centers that treat > 10 cases/y. Overall, 62% of the surgeons work in extra corporeal membrane oxygenation (ECMO) centers and 23% in fetal surgery centers. Prenatal work up and delivery: 47% surgeons request prenatal magnetic resonance imaging, 53% offer karyotyping, 22% perform a fetal intervention, 74% monitor head-to-lung ratio, and 55% administer maternal steroids. Delivery is via cesarean section for 47% surgeons, at 36 to 38 weeks for 71% surgeons, and in a tertiary care center for 94% of the surgeons.Postnatal Management A total of 76% surgeons report elective intubation, 65% start antibiotics preoperatively, and 45% administer surfactant. In case of refractory hypoxia, 66% surgeons consider ECMO with a variable course. Parenteral feeding is started preoperatively by 56% of the surgeons. Only 13% of the surgeons request contrast studies preoperatively to rule out malrotation.
Keywords: thoracoscopy; patch; Permacol; malrotation; muscle flap